Toward essential oil stewardship: strain-resolved evaluation of thyme oil activity against Pseudomonas aeruginosa - Brożyna, Malwina; Stępnicka, Zuzanna; Tymińska, Natalia; Dudek, Bartłomiej; Kapczyńska, Katarzyna; Matkowski, Adam; Sun, Yanfang; Tomczyk, Michał; Junka, Adam (Frontiers in Pharmacology, 2025)
The rising interest in essential oils (EOs) as antimicrobial agents demands evaluation frameworks that provide structured, reproducible assessments. In this study, we examined the strain-dependent response of Pseudomonas aeruginosa to pharmacopoeia-grade Thyme Essential Oil (obtained from Thymus vulgaris L., TEO) or polyhexamethylene biguanide antiseptic (PHMB) using a panel of ten genetically diversified strains in planktonic and biofilm forms, and by complementary in vitro models. Chemical composition of TEO was assessed using Gas Chromatography-Mass Spectrometry (GC–MS), and the main components were thymol, p-cymene, and γ-terpinene. Despite uniform test conditions, we observed striking inter-strain variability: TEO Minimal Inhibitory Concentrations (MICs) differed by up to 1,000-fold, and biofilm susceptibility profiles ranged from full tolerance to near-complete eradication. Notably, strains with low metabolic activity and sparse cell populations—but high matrix biomass—exhibited reduced responsiveness to TEO, while susceptibility to PHMB was more consistent, though not absolute. These findings highlight the critical influence of both microbial phenotype and agent formulation on antimicrobial outcomes. Rather than framing EOs as superior or inferior alternatives, our results advocate for their integration into a stewardship paradigm—one that values standardization, model-based evaluation, and informed formulation. In this context, we position essential oil stewardship not as a constraint but as a necessary evolution for their credible inclusion in antimicrobial strategies.